Reliability of diabetic neuropathy symptom and diabetic neuropathy examination scoring system for the diagnosis of diabetic peripheral neuropathy in type 2 diabetes mellitus patients - Ghosh, Labani M.; Mannari, Jyoti G. (International Journal of Research in Medical Sciences, 2019)
Background: This study aims to evaluate the reliability of the Diabetic Neuropathy Examination Score (DNE), 10-g Semmes-Weinstein Monofilament Examination and Quantitative Sensory Testing by Vibration Perception Threshold (VPT) in the diagnosis of diabetic polyneuropathy and seek a cost effective and reliable screening method in diabetic OPD and IPD against the gold standard of NCV. Methods: This study was carried out in 50 confirmed type 2 diabetic patients matched for age, sex, duration and ABI >0.9 irrespective of the presenting complaints. Patients with either limb amputation, other reasons for peripheral neuropathy, ABI <0.9, critical and comatose were excluded. A complete neurological assessment using a symptom questionnaire, Semmes Weinstein monofilament, vibration and thermal threshold perception analyzer was done and recorded. A score was given out of 20. The patients were retrograde subjected to NCV by a blinded technician and the readings were then compared to the scores. Results: The level of significance between the total neuropathy score and the presence of neuropathy (by NCV) was very significant (p<0.0001) with an association of 0.932. In patients with a mean total neuropathy score of 3.28,10.80 and 15.37, there was no, mild and severe levels of neuropathy in NCV respectively. Conclusions: There is correlation between the total neurological scores and NCV. Therefore, it can be used to screen all diabetic patients for earliest signs of diabetic neuropathy with sustainable results.